STEM education for students with disabilities - McDaniel, Angela (American Journal of STEM Education, 2024)
This study explores the benefits of STEM education for students with disabilities, emphasizing hands-on learning, inclusivity, and skill development. Based on teacher feedback from four regions of West Virginia, the findings highlight STEM's ability to enhance student engagement, collaboration, and confidence. Challenges such as resource limitations and class sizes are also discussed, alongside stakeholder recommendations to improve accessibility and effectiveness. The study underscores the transformative potential of inclusive STEM practices in fostering academic and personal growth for students with disabilities.